Application of the Assignment Method in Enhancing Student Learning Enthusiasm in the Subject of Jurisprudence - Sri Sulastri (Elementaria: Journal of Educational Research, 2023)
The objectives to be obtained from this research are: Want to know the effect of applying the recitation method in increasing student learning enthusiasm in fiqh subjects at mts Darul Falah Bongas Indramayu, want to know the obstacles faced in applying the recitation method (assignment assignments) in subject areas Jurisprudence study at Mts Darul Falah Bongas Indramayu, wanted to find out how effective the application of the recitation method (assignment assignments) was in increasing student enthusiasm for the subject of Fiqh study at MTs Darul Falah Bongas Indramayu. This type of research is field research that uses a descriptive qualitative method approach which uses the results obtained using the data collection method using the interview and documentation methods obtained when the researcher conducts research in class, and to obtain the results of the data needed the researcher conducts interviews and takes documentation. from students and teachers there. There is also a conclusion from this research that this method is very interesting where teachers and students not only do assignments in class but can be done anywhere, and children are quite enthusiastic about this method in their class when it is implemented.